2007
DOI: 10.3892/or.18.6.1551
|View full text |Cite
|
Sign up to set email alerts
|

Saliva as a biomarker for head and neck squamous cell carcinoma: In vitro detection of cytotoxic effects by using the plating efficiency index

Abstract: Abstract. Worldwide, the incidence of head and neck squamous cell carcinoma (HNSCC) is increasing. The development of an effective prevention program would provide a promising opportunity to control this disease. We applied the 'plating efficiency index' of Chinese hamster lung fibroblasts to demonstrate the presence of cytotoxic effects in saliva samples from cancer patients as well as from healthy probands. Correlations between individual risk factors and the cytotoxic effects of saliva specimens were analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The relevance of this pilot study lies in its possible development as a prognostic test with utility in the development of an effective prevention program to control head and neck cancer [ 8 ]. When compared with other highly diagnostic salivary tumour biomarkers, the advantages of this simple ELISA over the laboratory based 'in vitro detection of cytotoxic effects of saliva by using the plating efficiency index' [ 9 ] lie mainly in the ease of collection, simplicity of use and speed of results of the former. Despite this both tests have significant merit and may in fact be complementary.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of this pilot study lies in its possible development as a prognostic test with utility in the development of an effective prevention program to control head and neck cancer [ 8 ]. When compared with other highly diagnostic salivary tumour biomarkers, the advantages of this simple ELISA over the laboratory based 'in vitro detection of cytotoxic effects of saliva by using the plating efficiency index' [ 9 ] lie mainly in the ease of collection, simplicity of use and speed of results of the former. Despite this both tests have significant merit and may in fact be complementary.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that polymicrobial supragingival plaque may be a co‐factor in the development of oral carcinomas. The same authors, using a cell culture model, observed that saliva from patients with head and neck tumors had a higher cytotoxic effect on fibroblasts in comparison with saliva from healthy controls (Bloching et al , 2007a,b). Hence, the mutagenicity of saliva needs to be taken into account when considering the mechanisms involved in oral carcinomas.…”
Section: Pathological Mechanisms In Oral Carcinogenesismentioning
confidence: 98%
“…Saliva may also contain mutagenic compounds. Bloching et al (2007a,b) reported that a high dental plaque index and large number of decayed teeth were significantly correlated with Salmonella typhimurium genotoxicity (Ames test). The authors concluded that polymicrobial supragingival plaque may be a co‐factor in the development of oral carcinomas.…”
Section: Pathological Mechanisms In Oral Carcinogenesismentioning
confidence: 99%
“…Additionally, saliva specimens have been used in combination with the Ames test or a Chinese hamster V79 lung fibroblast cell line to investigate the genotoxic effects of smoking and alcohol consumption. exfoliated buccal cells have been used to monitor genetic damage in humans using the micronucleus test [ 81 , 82 ].…”
Section: Introductionmentioning
confidence: 99%